2000
DOI: 10.1046/j.1365-3024.2000.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of vesicular stomatitis New Jersey virus infection in mice by mosquito saliva

Abstract: Saliva of arthropod vectors can modulate vertebrate host immunological functions in many ways. To investigate if vesicular stomatitis New Jersey virus (VSNJ) infection could be potentiated by arthropod saliva, mice in three different age groups (3 days, 3 weeks, or > 8 months) were exposed to VSNJ-infected mosquitoes or were needle injected with an equivalent dose of VSNJ (titre 1.5-3 logs). Previous studies have demonstrated that VS viruses do not replicate in mice older than 3 weeks of age. Infection was mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 34 publications
1
67
1
1
Order By: Relevance
“…As described above, components of mosquito saliva have immunomodulatory activity, and thus, as a consequence, mosquito saliva can affect the anti-viral immune response and virus pathogenesis. Indeed, enhanced infection attributable to components of arthropod saliva is an accepted phenomenon, particularly with agents transmitted by ticks and sand flies (Cupp et al 1998, Edwards et al 1998, Limesand et al 2000, Nuttall and Labuda 2004, Theodos and Titus 1993. For example, when Leishmania major is inoculated with salivary gland extracts of sand flies, parasite burden, lesion size, and disease outcome are all amplified (Titus and Ribeiro 1988).…”
Section: Mosquito Associated Potentiation Of Arbovirus Transmission Amentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, components of mosquito saliva have immunomodulatory activity, and thus, as a consequence, mosquito saliva can affect the anti-viral immune response and virus pathogenesis. Indeed, enhanced infection attributable to components of arthropod saliva is an accepted phenomenon, particularly with agents transmitted by ticks and sand flies (Cupp et al 1998, Edwards et al 1998, Limesand et al 2000, Nuttall and Labuda 2004, Theodos and Titus 1993. For example, when Leishmania major is inoculated with salivary gland extracts of sand flies, parasite burden, lesion size, and disease outcome are all amplified (Titus and Ribeiro 1988).…”
Section: Mosquito Associated Potentiation Of Arbovirus Transmission Amentioning
confidence: 99%
“…Furthermore, studies with vesicular stomatitis virus (VSV) further demonstrate the potential for mosquito feeding or mosquito saliva to potentiate viral disease (Limesand et al 2000). Pathogenesis of VSV is age dependent: 3 day old mice infected with VSV by peripheral needleinoculation develop encephalitis and die, while older mice similarly infected show almost no signs of viral replication with 13% and 11% of 3-week old and adult (>8 months) mice, respectively, producing neutralizing antibody after needle inoculation.…”
Section: Mosquito Associated Potentiation Of Arbovirus Transmission Amentioning
confidence: 99%
“…Several studies have shown that arboviruses transmitted by mosquito bite or associated with mosquito saliva produce enhanced infection in vertebrate hosts compared to infection with the same viruses by needle inoculation (9,15,17,24,27). In contrast, other studies have shown no effect on arbovirus infection due to mosquito transmission (13,18,21,26).…”
mentioning
confidence: 99%
“…However, mDCs are different from many other cell types, such as fibroblasts, since they can rapidly respond to the incoming virus and do not require viral replication to initiate a type I IFN response (15), which may make these cells less susceptible to virally encoded interferon antagonists than other cell types. Therefore, other factors, such as immune-suppressive components of mosquito saliva, may also promote transmission to the vertebrate host (23,24,37). However, whether the virus derived from the mosquito differs from virus derived from mammalian cells in its ability to induce an antiviral response in mDCs or other cell types has not been evaluated.…”
mentioning
confidence: 99%